Brazilian version of the Kerlan-Jobe orthopedic clinic shoulder and elbow score: translation and cross-cultural adaptation - Felipe Marques da Silva; Raquel Lins de Sousa Lima; Gabriel Alves dos Santos; Germanna Medeiros Barbosa; Valéria Mayaly Alves de Oliveira; Danilo Harudy Kamonseki (São Paulo Medical Journal)
ABSTRACT BACKGROUND: The Kerlan-Jobe Orthopedic Clinic (KJOC) Shoulder and Elbow Score is commonly used to assess the functional status of athletes with conditions affecting the shoulder and elbow. However, a Brazilian Portuguese version of the KJOC questionnaire is currently unavailable. OBJECTIVES: This study aimed to develop a Brazilian Portuguese version of the KJOC questionnaire. DESIGN AND SETTING: This translation and cultural adaptation study was conducted at the Federal University of Paraíba, Brazil. METHODS: The procedures adopted in this study followed guidelines recommending translation by two independent translators, synthesis of the translations, back-translation performed by two native English-speaking translators, analysis by an expert committee, and pre-testing. The Portuguese version was tested with 32 athletes to assess their understanding of the assessment tool. Items were deemed adequate if they were understood by at least 90% of the athletes. RESULTS: The terms and expressions of some original items were modified to achieve better comprehensibility in the Brazilian context. No further modifications were necessary after the pre-test; all terms were comprehensible to over 90% of athletes. CONCLUSION: The translation and cultural adaptation of the KJOC questionnaire into Portuguese were completed, resulting in a Brazilian version of the scale. Further studies are needed to evaluate the reliability and validity of this scale.